The role of Leaders in Management Control - Radianto, Wirawan ED; Wijaya, Oscarius Yudhi Ari (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the role of leadership in the process of management control. The study will use qualitative method, namely phenomenology, with a single-case study strategy on a university setting. The data was collected from an in-depth interview, participatory observation, and document study. The sample group consists of the lecturers of the university. The result shows that the role of leadership is very important during the process of implementing a management control system. This research resulted in three big themes, which are inspiring leaders, participatory leaders, and leaders who are capable of handling human resources. This research also found that ‘trust’ is an important aspect in the management control system.